Hospodaření s dešťovou vodou v urbanizovaném území - Ličková, Nina (Vysoké učení technické v Brně,Fakulta architektury, 2015)
Sustainable development efforts include the protection of natural resources. Water is one of the principal life-giving elements. Water conservation should therefore be central not only to environment conservation, but also to urban planning concepts, details and technological solutions employing the water element.
Rainwater Management in Urban Areas
Keywords: Srážková voda; Akumulace; Vsakování